Mucoepidermoid carcinoma of the hard palate in a 9-year-old girl (clinical case) - К. А. Zolotarev; A. М. Mudunov; R. V. Shishkov; V. G. Polyakov; Yu. V. Alymov; V. Yu. Ivashkov; N. S. Babkin (Опухоли головы и шеи, 2019)
The objective of the work is to demonstrate the signs of mucoepidermoid carcinoma of the minor salivary glands in pediatric patients on a clinical example.Clinical case. In August 2017, a girl of 9 years old appeared in the area of the right half of the hard palate. The dentist at the place of residence diagnosed an abscess in the area of the hard palate, performed the lancing and drainage of the “abscess”, prescribed antibiotic therapy. After 3.5 months (in December 2017), hyperemia and an increase in the volume of the mucous membrane reappeared in the same zone. Reapplied to the dentist. The girl was sent to the Oral and Maxillofacial Surgery Department, where the hard palate formation was removed on 23.01.2018; according to histological examination a highly differentiated tumor of the hard palate was diagnosed. The girl was sent for a consultation to the N. N. Blokhin National Medical Research Center of Oncology, where histological preparations were reviewed: a fragment of the mucous membrane of the hard palate covered with squamous epithelium, with the growth of low-grade mucoepidermoid cancer (from the minor salivary glands of the hard palate). A biopsy of the postoperative scar 3 mm long and of the formation of a hard palate 1 mm in diameter was performed; during histological examination of the biopsy material tumor cells were not detected (the material was represented by fibrous tissue). Despite the biopsy results, taking into account the medical history, the results of a review of histological preparations, the rarity and high aggressiveness of the tumor, poor prognosis for relapse, lack of data for regional and distant metastases, at the concilium it was accepted the decision to conduct repeated surgery. In the Surgical Department No. 1 of the Research Institute of Pediatric Oncology and Hematology, N. N. Blokhin National Medical Research Center of Oncology on 13.03.2018 a resection of the hard palate was performed with plastic surgery of the defect with a mixed skin-muscle flap on the vascular pedicle.Conclusion. Mucoepidermoid cancer of the minor salivary glands of the hard palate in children and adolescents can be manifested by the presence of a slowly growing, painless, pale blue tumor. For a correct clinical and morphological diagnosis, a biopsy of the tumor is necessary, further the removal of the tumor is recommended with resection of the hard palate, in view of the high risk of tumor spreading in the thickness of the bone.